Bulk metallic glassy surface native oxide: Its atomic structure, growth rate and electrical properties. (15th September 2015) - Louzguine-Luzgin, D.V.; Chen, C.L.; Lin, L.Y.; Wang, Z.C.; Ketov, S.V.; Miyama, M.J.; Trifonov, A.S.; Lubenchenko, A.V.; Ikuhara, Y.
Graphical abstract: Abstract: Formation of a native oxide layer on the surface of bulk metallic glasses (BMGs) influences significantly the nanoscale tribological properties and mechanical behavior of the BMGs used in nanodevices. However, our knowledge of the native oxidation process on the BMG surface and structure of the corresponding oxides remains limited because the oxide layer is very thin. Here we conducted a combined state-of-the-art experimental technique study of the atomic structure, oxidations states and electrical conductivity of the native surface oxides on a CuZrAl BMG formed at ambient conditions by aberration-corrected scanning transmission electron microscopy (STEM), X-ray photoelectron spectroscopy (XPS) and conductive atomic force microscopy (AFM). This allowed shedding light on the atomic structure, metal oxidation state, growth behavior and nanoscale electrical properties of the surface oxide. The conductive AFM measurements reveal that the electrical conductivity of the native oxide layer transits from the initially metallic to a nonlinear one after some air exposure, and finally changes to insulative state. These findings represent a significant step forward in the knowledge of surface oxides and open up the possibility of fabricating nanoscale electrical devices based on BMGs with controllable conductivity.